Clinical characteristics of liver transplant recipients with COVID-19 and analysis of risk factors for the severe disease - Fu, Sunya; Chen, Dawei; Zhang, Yuqin; Wu, Mingjie (The Journal of Infection in Developing Countries, 2024)
Introduction: Liver transplant (LT) recipients were at a high risk of infection during the coronavirus disease 2019 (COVID-19) pandemic. Our purpose was to compare the clinical characteristics of severe and non-severe groups of LT recipients with COVID-19, and to analyze their risk factors for severe disease. Methodology: 79 LT recipients with COVID-19 were divided into a non-severe group (n = 60) and a severe group (n = 19), and differences in clinical characteristics, laboratory tests, and chest computed tomography (CT) performance were analyzed. Logistic regression was used to identify risk factors with severe COVID-19. Receiver operating characteristic (ROC) curves were plotted and the area under curve (AUC) values were calculated to assess the predictive value for severe COVID-19. Results: Age was statistically different (p < 0.001) between the two groups. The difference in neutrophil-to-lymphocyte ratio (NLR), serum creatinine (Scr), D-dimer, urea, C-reactive protein (CRP), lactate dehydrogenase (LDH), and the number of lung segments involved in inflammation between the two groups were statistically significant (p < 0.05). The results revealed that age (OR = 1.255, 95% CI 1.079-1.460), NLR (OR = 1.172, 95% CI 1.019-1.348), and Scr (OR = 1.041, 95% CI 1.016-1.066) were independent risk factors for severe COVID-19. The ROC results showed that high values for age, NLR and Scr predicted severe COVID-19, with AUC values of 0.775, 0.841 and 0.820, respectively, and 0.925 for the three factors combined. Conclusions: Advanced age, and elevated NLR and Scr are independent risk factors for severe COVID-19 in LT recipients.